Polygenic Risk Scores have high diagnostic capacity in ankylosing spondylitis. Issue 9 (20th April 2021) - Li, Zhixiu; Wu, Xin; Leo, Paul J; De Guzman, Erika; Akkoc, Nurullah; Breban, Maxime; Macfarlane, Gary J; Mahmoudi, Mahdi; Marzo-Ortega, Helena; Anderson, Lisa K; Wheeler, Lawrie; Chou, Chung-Tei; et al.
Abstract : Objective: We sought to test the hypothesis that Polygenic Risk Scores (PRSs) have strong capacity to discriminate cases of ankylosing spondylitis (AS) from healthy controls and individuals in the community with chronic back pain. Methods: PRSs were developed and validated in individuals of European and East Asian ethnicity, using data from genome-wide association studies in 15 585 AS cases and 20 452 controls. The discriminatory values of PRSs in these populations were compared with other widely used diagnostic tests, including C-reactive protein (CRP), HLA-B27 and sacroiliac MRI. Results: In people of European descent, PRS had high discriminatory capacity with area under the curve (AUC) in receiver operator characteristic analysis of 0.924. This was significantly better than for HLA-B27 testing alone (AUC=0.869), MRI (AUC=0.885) or C-reactive protein (AUC=0.700). PRS developed and validated in individuals of East Asian descent performed similarly (AUC=0.948). Assuming a prior probability of AS of 10% such as in patients with chronic back pain under 45 years of age, compared with HLA-B27 testing alone, PRS provides higher positive values for 35% of patients and negative predictive values for 67.5% of patients. For PRS, in people of European descent, the maximum positive predictive value was 78.2% and negative predictive value was 100%, whereas for HLA-B27, these values were 51.9% and 97.9%, respectively. Conclusions: PRS have higher discriminatory capacity for AS than CRP, sacroiliac MRI or HLA-B27 status alone. For optimal performance, PRS should be developed for use in the specific ethnic groups to which they are to be applied.